2021
DOI: 10.1017/jfm.2021.518
|View full text |Cite
|
Sign up to set email alerts
|

Deterministic and stochastic bifurcations in two-dimensional electroconvective flows

Abstract: Abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 66 publications
0
5
0
Order By: Relevance
“…2015; Zhang 2016; Feng et al. 2021). Since a strong injection regime has been considered in this work, we take .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…2015; Zhang 2016; Feng et al. 2021). Since a strong injection regime has been considered in this work, we take .…”
Section: Resultsmentioning
confidence: 99%
“…The typical value of Fe (inverse of charge diffusion) for the real dielectric fluids lies within the range 10 3 -10 4 (Pérez & Castellanos 1989), thus we choose an intermediate value Fe = 5 × 10 3 in this work, except in the section where we study its effect. Previous works often neglected this charge diffusion term (Pérez et al 2009;Wu et al 2013;Perri et al 2020), but it has been shown that the charge diffusion has a non-negligible effect on the linear stability and bifurcation in EHD flows (Zhang et al 2015;Zhang 2016;Feng et al 2021). Since a strong injection regime has been considered in this work, we take C = 5.…”
Section: Resultsmentioning
confidence: 99%
“…However, in these algorithms, some free parameters must be introduced, such as the embedding dimension and delay time. To characterize the chaotic motions in the EC in a more systematic way and avoid assigning free parameters, the method of Wolf et al (1985) has been widely used recently (Feng et al 2021;Huang et al 2021). Moreover, Li et al (2020) first introduced this method to investigate the transition process from laminar to chaotic flow in ETC.…”
Section: Bifurcations and Chaos In Etcmentioning
confidence: 99%
“…In particular, Wu et al (2013) studied the critical bifurcation of EHD flow in a 2-D finite container without considering the charge diffusion effect. Deterministic and stochastic bifurcations in EHD flow of a dielectric liquid between two parallel plates was investigated by Feng et al (2021). They tried to reduce the discrepancy of the linear instability criteria between experiment and theory by considering stochastic boundary conditions.…”
Section: Stability Analysis Of Ehd Flowmentioning
confidence: 99%
“…Deterministic and stochastic bifurcations in EHD flow of a dielectric liquid between two parallel plates was investigated by Feng et al. (2021). They tried to reduce the discrepancy of the linear instability criteria between experiment and theory by considering stochastic boundary conditions.…”
Section: Introductionmentioning
confidence: 99%